Mortality of Conotrachelus humeropictus in response to combined application of the nematode Steinernema brazilense and the fungus Beauveria bassiana - Simi, Lucas Detogni [UNESP]; Leite, Luís Garrigós; Trevisan, Olzeno; Costa, José Nilton Medeiros; Oliveira, Leandro Ezequiel; Schmidt, Fabio Silber; Bueno, Roselaine Nunes Da Silva; Batista, Antonio (Instituto Biológico, 2018)
The fruit borer Conotrachelus humeropictus is one of the most important pests of the cupuaçu crop, and can promote yield losses of around 50%. The present study involved the selection of Beauveria bassiana isolates on Conotrachelus psidii larvae, which was used as test insect due to its taxonomic closeness to C. humeropictus. In order to assess their interaction using combined application, we studied the ability of the nematode to carry conidia of B. bassiana and Metarhizium anisopliae to soil layers. This study also aimed to establish a biological control method for cupuaçu borer with the use of the fungus B. bassiana at 10 kg/ha and the entomopathogenic nematode Steinernema brazilense at 1, 3, 9, and 27 IJ/cm2, applied as single and combined treatments. In the selection of B. bassiana strains for C. psidii, the IBCB 276 and IBCB 165 isolates were the most promising ones, causing 86 and 84% mortality, respectively. The IBCB 276 strain was applied in the field to control C. humeropictus. In the study of carriage of conidia in soil, the nematode S. brazilense was found to be capable of carrying conidia of B. bassiana to deep 7 to 10 cm soil layers. This was not observed with M. anisopliae, found only in the topsoil. In field trials against C. humeropictus larvae, B. bassiana promoted 15.6% mortality. The nematode promoted 60.0% mortality at the highest concentration used, and their combined use with B. bassiana (10 kg/ha) increased mortality to 65.6%, with an additive interaction observed between the two entomopathogens.

A broca-do-cupuaçu, Conotrachelus humeropictus, é uma das principais pragas da cultura, podendo ocasionar perdas de 50% na produção. O presente trabalho envolveu uma seleção prévia de isolados de Beauveria bassiana em larvas de Conotrachelus psidii, utilizado como inseto teste por ser próximo taxonomicamente à C. humeropictus. Com o objetivo de avaliar causa-efeitos da interação na aplicação combinada, foi estudada a capacidade do nematoide carrear conídios de B. bassiana e Metarhizium anisopliae pelas camadas de solo. O trabalho também objetivou avaliar o controle biológico da broca-do-cupuaçu, através do uso do fungo B. bassiana 10 kg/ha, e do nematoide entomopatogênico Steinernema brazilense 1, 3, 9 e 27 JI/cm2, aplicados em tratamentos isolados e em combinação. Na seleção de isolados de B. bassiana para C. psidii, os isolados IBCB 276 e IBCB 165 foram os mais promissores, causando, respectivamente, 86 e 84% de mortalidade confirmada. O isolado IBCB 276 foi aplicado em campo para controlar C. humeropictus. No estudo de carreamento de conídios, o nematoide S. brazilense foi capaz de carrear conídios de B. bassiana para a camada de 7 a 10 cm de profundidade no solo. A mesma ação não foi observada com M. anisopliae, encontrado somente na camada superficial do solo. Nos ensaios de campo contra C. humeropictus, B. bassiana promoveu 15,6% de mortalidade. O nematoide promoveu 60,0% de mortalidade na maior concentração utilizada e, na combinação dessa concentração do NEP com B. bassiana (10 kg/ha), a mortalidade atingiu 65,6%, observando-se interação aditiva entre os dois entomopatógenos.
Mortalidade de Conotrachelus humeropictus pela aplicação combinada do nematoide Steinernema brazilense com o fungo entomopatogênico Beauveria bassiana
Keywords: biological control; microbial control; interaction; combined use; controle biológico; controle microbiano; interação; uso combinado